The sculpture of F.E. McWilliam - Ferran, Denise; Holman, Valerie (British sculptors and sculpture series., 2012)
A highly respected sculptor, F.E. McWilliam (1909-1992) was described by Bryan Robertson in 1992 as 'one of the truest artists to work in England this century'. Yet despite achieving great acclaim in his lifetime, McWilliam's contribution to modern art has been unduly neglected in recent years.